2013
DOI: 10.1111/aogs.12065
|View full text |Cite
|
Sign up to set email alerts
|

No reduction of manual removal after misoprostol for retained placenta: a double‐blind, randomized trial

Abstract: Objective. To test the effect of 800 lg of misoprostol orally on the prevention of manual removal of retained placenta. Design. Multicenter, doubleblinded, placebo-controlled, randomized trial. Setting. One university and one non-university teaching hospital in the Netherlands. Sample. 99 women with retained placenta (longer than 60 min after childbirth) in the absence of postpartum hemorrhage. Methods. Eligible women were administered either 800 lg of misoprostol or placebo orally. Main outcome measures. Numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…A meta-analysis of two small RCTs of oral misoprostol, a synthetic prostaglandin, found a reduction in the need to perform manual removal compared with placebo (0.61, 0.41 to 0.90; 84 participants). 4 However, other relevant outcomes including postpartum haemorrhage, infection, surgical evacuation of retained products of placenta, and maternal mortality were not reported.…”
Section: Intraumbilical Intravenous and Oral Prostaglandinmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of two small RCTs of oral misoprostol, a synthetic prostaglandin, found a reduction in the need to perform manual removal compared with placebo (0.61, 0.41 to 0.90; 84 participants). 4 However, other relevant outcomes including postpartum haemorrhage, infection, surgical evacuation of retained products of placenta, and maternal mortality were not reported.…”
Section: Intraumbilical Intravenous and Oral Prostaglandinmentioning
confidence: 99%
“…The comparator should be standard care based on current practice (intraumbilical oxytocin) Outcome: Primary: delivery of the placenta within 60 minutes, avoiding the need for manual removal of the placenta. Secondary: postpartum haemorrhage, adverse events, and side effects Design: Multi-centre randomised controlled trial with factorial design Table Table 1| Meta-analysis of the effectiveness and safety of interventions to treat retained placenta 4 …”
Section: Recommendations For Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Seven studies met the inclusion criteria [12][13][14][15][16][17][18] ; nine trials were excluded because they were not randomized controlled trials (n=6), were not original articles (n=2), or were a preliminary report (n=1). The included studies are described in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…For the random sequence generation domain, only four trials [12][13][14][15] appropriately reported the method used and were assessed as low risk of bias. For allocation concealment, five trials [14][15][16][17][18] adequately implemented a valid concealment of allocation method by using sequentially numbered sealed envelopes or containers with a similar appearance, making selection bias at enrollment unlikely.…”
mentioning
confidence: 99%